(untitled) (Research, Society and Development, 2020)
Wastewater or sewage water is commonly defined as that which was discarded in the environment after its domestic, commercial or industrial use. In order to take advantage of this resource, we sought to evaluate its effect on the initial growth of sugarcane varieties used in energy generation and sugar production. For the planting, the use of a yolk wheel. The statistical design adopted was that of random blocks in a 2 x 4 factorial arrangement, corresponding to two varieties of sugarcane in four types of water for irrigation, namely: I- supply water, II- supply water with addition of nitrogen, III- waste water and IV- waste water with nitrogen addition. The variables analyzed were: leaf area, number, width and length of the leaves, number, height and average stem diameter, fresh and dry mass of the stem, fresh and dry mass of the leaf and total fresh and dry mass of the aerial part. The data were submitted to analysis of variance, the means grouped by the Scott and Knott test at 5% probability and the genetic parameters were estimated. Significant differences were detected between the varieties, indicating differential behavior to water types. It was also found that, in some variables, where the crop was irrigated with wastewater, the performance was superior. It was concluded that the good performance presented by the studied varieties was due, for the most part, to genetic effects and that the use of wastewater may prove to be a viable alternative during the initial growth of sugarcane.